Evaluation of the course of the early postoperative period after surgery endovascular abdominal aortic aneurysm elimination by biochemical tests - Gorzelak, Martyna; Pierzak, Monika; Chrut, Aneta (Journal of Education, Health and Sport, 2018)
Summary Admission: Abdominal aortic aneurysm occurs in 4-9% of men and 12% of women over 65 years of age, and its rupture is the cause of 10 deaths in developed countries. Perioperative mortality in the event of a ruptured aneurysm is 20-50%, and remains unchanged regardless of the methods of treatment, while in the surgical treatment of patients under elective with the work of J. N. Volodos and Pariodiego obtained vast improvement early results. Late results for endovascular methods are not as good, it is the subject of numerous multicenter studies. The current mortality rate of patients treated with endovascular means remains below 1%. Despite lower overall mortality continues to happen all sorts of complications such as local and general. Objective of the work: Rating Running the early postoperative period after surgery endovascular abdominal aortic aneurysm elimination with selected biochemical indices. Material and methods: The patient admitted in elective office in the diagnosis of abdominal aortic aneurysm endovascular purpose of supply. Results: The course of post-operative patient in a test can not be described as complicated. Control arteriography showed off correct an aneurysm, without leakage. Conclusions: Postoperative care is a continuation of surgical treatment and significantly determines the scope of the safety of the patient and the risk of developing complications. Accurate and systematic observation of patients after EVAR allows immediate detection and treatment of complications occurring. Keywords: abdominal aortic aneurysm, endovascular elimination of abdominal aortic aneurysm, early postoperative period.